Estrogenic Component in Preventive Menopausal Hormonal Therapy - Makhmatkulova G. M.; Juraboev I. A.; Sodikov S. S. (Scholars Digest Publishing, 2023)
One of the elements of the effect of estrogens on the psycho-emotional state is the connection with the serotonergic system of the brain involved in mood regulation. Nowadays, women spend a significant part of their own lives in the postmenopausal stage, in conditions of a lack of sex hormones, which negatively affects the quality of life and multiplies the threat of serious diseases. Menopausal hormone replacement therapy is designed to reduce the risks of life, it is able to prolong and improve the lives of females. Day after day, life expectancy and the aging of the population grow rapidly. Females are characterized by a higher sensitivity. For example, when there are conditions of lack of sex hormones, their body becomes brittle, as well as susceptible to various diseases. In order to prevent fundamental changes in the activity of the body and its concepts of eliminating previously appeared signs and improving the features of existence, menopausal hormone replacement treatment is needed.
Keywords: Menopause, hormone deficiency, combination hormone therapy, neurodegenerative conditions, metabolic syndrome.